“An Icelandic Driver”: J. Magnús Bjarnason’s Story as a History of Immigrant Hierarchy and Antisemitism in Nineteenth-Century Halifax: An Introduction - Lalonde, Jay L. (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2023)
This introduction to “An Icelandic Driver” by Jóhann Magnús Bjarnason aims to provide a critical context for reading the text. The story portrays Halifax as a city of immigrants and depicts the otherwise underdiscussed histories of urban Icelandic immigration. It also relies, however, on the structures of racialized immigrant hierarchy, antisemitism, and Black erasure. This introduction provides background information about Bjarnason’s life and work, and critically analyzes the ways in which his text thematizes national identity and community. It also aims to rectify the stereotypical depictions of Jewish characters in the story, as well as the complete erasure of Black Haligonians, by providing accounts of some of the many Jewish and Black histories of Halifax and Nova Scotia that Bjarnason chooses to omit.